A phase I clinical trial to evaluate the tolerability and safety of an allogeneic iPSC-derived iNKT cell and α-GalCer-pulsed autologous DC combination therapy for patients with recurrent and advanced head and neck cancer: A study protocol - Tomoya Kurokawa; Tomohisa Iinuma; Haruna Ebisu; Tomoha Yanagidaira; Yosuke Inaba; Tadami Fujiwara; Yoko Hattori; Tominaga Fukazawa; Takahiro Aoki; Haruhiko Koseki; Hideki Hanaoka; Toyoyuki Hanazawa; et al. (PLoS ONE, 2026)
Natural killer T (NKT) cells show intense tumor-killing activity through direct and indirect pathways. However, humans have less than 0.01% of NKT cells in the peripheral blood, making it difficult to apply NKT cells for cancer treatment. We have successfully produced invariant NKT cells derived from induced pluripotent stem cells (iPSC-iNKT cells) and demonstrated the tolerability of this product in a previous phase 1 clinical trial. Although the iPSC-iNKT cells showed substantial anti-tumor activity against various tumor cell types when combined with α-Galactosylceramide-pulsed autologous dendritic cells (DC/Gal) in non-clinical experiments, the tolerability of this combination therapy for humans has not demonstrated yet. Thus, we planned this first-in-human phase 1 open-label clinical trial to demonstrate data on tolerability and safety, as well as explore the immunological changes that occur following this combination treatment. We hypothesize that the sequential induction of nasal submucosal DC/Gal injection and intra-arterial administration of the iPSC-iNKT cells is tolerable and has a favorable safety profile for cancer patients. This trial provides vital and fundamental information for next-phase clinical trials and future applications of iPSC-iNKT cells for various cancer patients (jRCTa030220741; URL: https://jrct.mhlw.go.jp/en-latest-detail/jRCTa030220741 ).